Light scattering in LiCoPO₄ single crystal: analysis of the vibrational spectrum - Fomin, V.I.; Gnezdilov, V.P.; Kurnosov, V.S.; Peschanskii, A.V.; Eremenko, V.V.; Rivera, J.-P.; Gentil, S. (Физика низких температур, 1999)
In a single crystal of LiCoPO₄ Raman scattering has been studied in a wide temperature range. Thirty-two of the 36 Raman-active vibrational modes predicted by group-theory analysis were detected. The experimental lines are identified on the basis of their polarization rules, frequency position, and temperature behavior.